Simple Past Tense Learning Using Enjoy English for Nusantara Application: Pembelajaran Simple Past Tense Melalui Aplikasi Enjoy English for Nusantara - Amelia, Ana; Lisdiani, Dina; Yulia, Rini; Primayana, Muhammad Reiva; Subastian, Yopi; Saepurohman, Aam Ahmad; Pratama, Encep Rafli Adi Putra (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: English grammar mastery remains a foundational requirement for EFL learners, particularly in expressing past events through simple past tense structures. Specific Background: Junior high school students frequently encounter difficulties in vocabulary recall, grammatical accuracy, and sequencing past events, especially within contextual learning topics such as No Littering. Knowledge Gap: Although digital learning media and grammar instruction have been widely discussed, limited studies describe the use of context-based interactive applications integrated with audio, simulation, and drill activities at the junior high school level. Aims: This study aims to identify students’ learning problems, describe the implementation of the Enjoy English for Nusantara application, and examine students’ language skill development during its use. Results: The findings show improvements in vocabulary retention, grammatical accuracy, event sequencing, and students’ confidence in oral English, supported by observations, interviews, and learning documentation. Audio from native speakers familiarized students with sentence patterns, while drill activities strengthened language habits. Novelty: This study presents an integrated digital application combining contextual material, native-speaker audio, interactive simulation, and drill practice for simple past tense learning. Implications: The results suggest that interactive digital learning media may serve as an alternative approach for junior high school English instruction, supporting student engagement and structured language practice. Highlights • Students demonstrated stronger vocabulary recall and sentence construction accuracy• Interactive simulation supported clearer sequencing of past events• Audio and drill activities encouraged greater student participation in oral practice Keywords Simple Past Tense; EFL Learners; Digital Learning Application; Interactive Learning; Grammar Practice